Effectiveness of antiepileptic therapy in patients with PCDH19 mutations. (February 2016) - Lotte, Jan; Bast, Thomas; Borusiak, Peter; Coppola, Antonietta; Cross, J. Helen; Dimova, Petia; Fogarasi, Andras; Graneß, Irene; Guerrini, Renzo; Hjalgrim, Helle; Keimer, Reinhard; Korff, Christian M.; et al.
Highlights: Bromide and clobazam turned out to be the most effective drugs after 3 and 12 months. Three-quarters of our patients were seizure-free for at least 3 months, half of them for one year and two even for over 10 years. Assessing the effectiveness of drugs is difficult because an age-dependent and spontaneous seizure remission must be considered. Abstract: Purpose: PCDH19 mutations cause epilepsy and mental retardation limited to females (EFMR) or Dravet-like syndromes. Especially in the first years of life, epilepsy is known to be highly pharmacoresistant. The aim of our study was to evaluate the effectiveness of antiepileptic therapy in patients with PCDH19 mutations. Methods: We report a retrospective multicenter study of antiepileptic therapy in 58 female patients with PCDH19 mutations and epilepsy aged 2–27 years (mean age 10.6 years). Results: The most effective drugs after 3 months were clobazam and bromide, with a responder rate of 68% and 67%, respectively, where response was defined as seizure reduction of at least 50%. Defining long-term response as the proportion of responders after 12 months of treatment with a given drug in relation to the number of patients treated for at least 3 months, the most effective drugs after 12 months were again bromide and clobazam, with a long-term response of 50% and 43%, respectively. Seventy-four percent of the patients became seizure-free for at least 3 months, 47% for at least one year. Significance: The most effective drugs in patients with PCDH19 mutations were bromide and clobazam. Although epilepsy in PCDH19 mutations is often pharmacoresistant, three quarters of the patients became seizure-free for at least for 3 months and half of them for at least one year. However, assessing the effectiveness of the drugs is difficult because a possible age-dependent spontaneous seizure remission must be considered.